2012
DOI: 10.3892/mmr.2012.908
|View full text |Cite
|
Sign up to set email alerts
|

Differential effects of mechanical strain on osteoclastogenesis and osteoclast-related gene expression in RAW264.7 cells

Abstract: Abstract. Mechanical strain plays a critical role in the formation, proliferation and maturation of bone cells. However, little is known about the direct effects of different magnitudes of mechanical strain on osteoclast differentiation. The aim of the present study was to investigate how the fusion and activation of osteoclasts can be regulated by mechanical strain magnitude using the RAW264.7 mouse monocyte/ macrophage cell line as an osteoclast precursor. Mechanical strain (substrate stretching) was applied… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Hayakawa et al [15] previously revealed that the expression of both cathepsin K and matrix metalloproteinase-9 in RAW264.7 cells pre-incubated with RANKL was increased by stimulation with compressive force (~0.3 g/cm 2 ). Xu et al [34] reported that the effects of mechanical strain on the expression of matrix metalloproteinase-9 and cathepsin K differed, with mechanical strains of 2000 and 2500 μɛ inducing matrix metalloproteinase-9 expression, while cathepsin K expression was not affected by mechanical strain of this magnitude. Mechanical stimulation from physical activity, exercise, and adaptive stress contributes to bone tissue homeostasis [4,5].…”
Section: Discussionmentioning
confidence: 99%
“…Hayakawa et al [15] previously revealed that the expression of both cathepsin K and matrix metalloproteinase-9 in RAW264.7 cells pre-incubated with RANKL was increased by stimulation with compressive force (~0.3 g/cm 2 ). Xu et al [34] reported that the effects of mechanical strain on the expression of matrix metalloproteinase-9 and cathepsin K differed, with mechanical strains of 2000 and 2500 μɛ inducing matrix metalloproteinase-9 expression, while cathepsin K expression was not affected by mechanical strain of this magnitude. Mechanical stimulation from physical activity, exercise, and adaptive stress contributes to bone tissue homeostasis [4,5].…”
Section: Discussionmentioning
confidence: 99%
“…Osteoblasts directly respond to mechanical stimulation by changes in numerous signaling networks [ 142 ], although they are less responsive than osteocytes. Osteoclasts have not been studied as extensively, but in general, it has been shown that mechanical stimulation reduces osteoclast formation and bone resorption when other factors are constant, consistent with the theme that mechanical stimulation is bone anabolic [ 143 , 144 , 145 ]. With the recent studies that suggest that osteoclasts are full partners, with osteoblasts and osteocytes, in signaling involved in the maintenance of the bone [ 18 ], new studies examining how mechanical signaling affects intercellular signals generated by osteoclasts are warranted.…”
Section: Direct Response Of Osteoclasts To Mechanical Stimulationmentioning
confidence: 94%
“…A human-derived breast cancer cell line, MDA-MB-231 (HTB-26), and a mouse macrophage cell line, RAW264.7 (TIB-71), both obtained from the American Type Culture Collection (ATCC), were used in the present study. The RAW 264.7 cells are known as preosteoclast cells, which readily differentiate into osteoclasts upon exposure to receptor activator for nuclear factor-κB ligand (RANKL) ( 23 ). Cells were cultured in Dulbecco's modified Eagle's medium (DMEM) supplemented with 10% fetal bovine serum (FBS), 100 U/ml penicillin and 100 µ g/ml streptomycin (all from Sigma-Aldrich; Merck KGaA), and maintained in a humidified atmosphere with 5% CO 2 at 37°C.…”
Section: Methodsmentioning
confidence: 99%